1. Zapisz wyrażenia, nie używając nawiasów. Zredukuj wyrazy podobne.
a) 2a +(3a - 7)=
b) x - (2x - 3)=
c) 3x - (y -2x)=
d) -(3a+6)-4 =
e) -(2x-1)-(3x+1)=
f) (4a-7b)-(2a+3b)=
g) (2p-r)+ (2r-p)=
h) (x+y)+(x-z)+(z-y)=

NIE CHCĘ SAMYCH OBLICZEŃ

2

Odpowiedzi

2010-03-03T18:49:16+01:00
2a +(3a - 7)=2a+3a-7=5a-7
x - (2x - 3)=x-2x+3=-x+3
3x - (y -2x)=3x-y+2x=5x-y
-(3a+6)-4=-3a-6-4=-3a-10
-(2x-1)-(3x+1)=-2x+1-3x-1=-5x
(4a-7b)-(2a+3b)=4a-7b-2a-3b=2a-4b
(2p-r)+ (2r-p)=2p-r+2r-p=p+r
(x+y)+(x-z)+(z-y)=x+y+x-z+z-y=2x
5 4 5
2010-03-03T18:49:42+01:00
A) 2a +(3a - 7)= 2a + 3a - 7 = 5a - 7
b) x - (2x - 3)= x - 2x + 3 = x + 3
c) 3x - (y -2x)= 3x - y + 2x = 5x - y
d) -(3a+6)-4 = - 3a - 6 - 4 = -3a - 10
e) -(2x-1)-(3x+1)= - 2x + 1 - 3x -1 = -5x
f) (4a-7b)-(2a+3b)= 4a - 7b - 2a - 3b = 2a - 10b
g) (2p-r)+ (2r-p)= 2p - r + 2r-p= r+p
h) (x+y)+(x-z)+(z-y)= x+y+x-z+z-y = 2x
8 4 8